SUITABILITY MODEL BASED ON GIS AND MCDA FOR SPATIAL DISTRIBUTION OF SETTLEMENTS IN DIFFERENT GEOGRAPHIC ENVIRONMENTS - Abdullah, Nashwan Shukri (European Scientific Journal, ESJ, 2014)
The spatial structure of settlements in Duhok Governorate in Iraq has changed over the last two decades, far from the comprehensive spatial planning. The study was carried out in two different geographical environments, one is in plain area (Semil), and the other is in mountainous area (Amidy). This study aims to detect the spatial distribution patterns of settlements in each district, and to develop a spatial suitability model for settling in each part of the study area. This model helps researchers, governmental sectors, and decision makers to develop a general framework of rural development. Inter-disciplinary methodology has been used, based on combination between MCDA (Mulit- Criteria Decision Analysis) and GIS capabilities. The process was conducted based on eleven criteria, which were prepared using ENVI, ArcGIS10.1, and Global Mapper15. The AHP (Analytical Hierarchy Process) method were used to build weights for criteria, while WLC (weighted linear combination) approach was implemented to formulate suitability models in each district. The study demonstrates a slight discrepancy between the spatial pattern of existing suitability potential and the actual distribution of settlements. According to the model, about 53.7% of study area is either suitable or highly suitable to build new settlements, and the remaining area 46.3% rated as either moderately, poorly suitable or unsuitable. However, the study found clearly different between Amidy and Semil. The model used in this study is applicable elsewhere in Iraqi Kurdistan Region.